Single-component adhesive fluorosilicone gel and preparation method thereof
By combining vinyl fluorosilicone oil, hydrofluorosilicone oil on the end side, coupling agent and platinum catalyst in a specific proportion, a single-component bonded fluorosilicone gel is prepared, which solves the problem that it is difficult to find a single-component fluorosilicone gel with good high temperature resistance, oil resistance and bonding properties in the prior art, and achieves efficient curing and excellent comprehensive performance.
Patent Information
- Application Number
- CN202411893316.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-04
AI Technical Summary
How to find a one-component bonded fluorosilicone gel that can be completely cured within 150°C and above half an hour, with good high temperature resistance, oil resistance and good bonding properties to PCB substrates.
One-component bonded fluorosilicone gel is prepared by combining vinyl fluorosilicone oil, hydrofluorosilicone oil on the end, coupling agent and platinum catalyst in a specific mass part, and mixed defoaming is performed, and a co-solvent can be optionally added to improve compatibility and transparency.
The single-component bonded fluorosilicone gel is fully cured within 150°C and above half an hour, and has excellent high temperature resistance, oil resistance and good bonding properties to PCB substrates, while improving the transparency of the gel.
Smart Images

Figure BDA0005201135260000011 
Figure BDA0005201135260000021 
Figure BDA0005201135260000022
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a single-component bonding fluorosilicone gel and a preparation method thereof. Background Art
[0002] Potting glue is to use equipment or manual methods to pour silicone potting glue, polyurethane potting glue, epoxy resin potting glue, etc. into devices equipped with electronic components and circuits, and solidify them into thermosetting polymer insulating materials with excellent performance under normal temperature or heating conditions, so as to achieve the purpose of bonding, sealing, potting and coating protection. Generally, potting glue used for electronic devices can be called electronic potting glue. Electronic potting glue can be divided into silicone potting glue, thermal conductive potting glue, epoxy resin potting glue, polyurethane potting glue, LED potting glue and other types. Electronic potting glue is liquid before curing and has fluidity. The viscosity of the glue varies according to the material, performance and production process of the product; the potting glue can only realize its use value after it is completely cured. After curing, it can play the role of waterproof, moisture-proof, dust-proof, insulation, thermal conductivity, confidentiality, corrosion resistance, temperature resistance, shock resistance and so on. Silicone potting glue refers to a type of electronic potting glue made of silicone rubber, including single-component silicone potting glue and two-component silicone potting glue. Silicone potting compound has the advantages of wide applicable temperature range, no deformation during processing, and excellent electrical properties. Addition-type silicone potting compound is usually composed of vinyl silicone oil, hydrogen silicone oil, platinum catalyst, etc., and other fillers such as fumed silica, iron oxide, etc. can be added according to different uses, or silicone resin can be added as a filler. How to find a single-component adhesive fluorosilicone gel that can be well cured, has good high temperature resistance and oil resistance, and has good bonding properties to plastics is a technical problem that needs to be solved urgently. Summary of the invention
[0003] In view of the above problems, the present invention provides a one-component adhesive fluorosilicone gel and a preparation method thereof.
[0004] The present invention provides a one-component adhesive fluorosilicone gel, comprising the following components in parts by mass:
[0005]
[0006]
[0007] Optionally, the one-component adhesive fluorosilicone gel further comprises 1 to 2 parts of a co-solvent;
[0008] The structural formula of the cosolvent is shown below:
[0009]
[0010] Among them, n is 2 to 6.
[0011] Optionally, the molar content of vinyl in the vinyl fluorosilicone oil is 0.1 to 1%; the molar content of fluorine is 5 to 20%, preferably 10 to 20%, and more preferably 16 to 20%.
[0012] Optionally, the mass fraction of active hydrogen in the end-side hydrogen-containing fluorosilicone oil is 1 to 10%; the molar content of fluorine is 5 to 20%, preferably 16 to 20%.
[0013] Optionally, the coupling agent is one or more selected from fluorine-containing silane coupling agents.
[0014] Optionally, the structural formula of the coupling agent is as follows:
[0015]
[0016] Among them, R 1 , R 2 is methyl and / or ethyl, and n is 2-6.
[0017] Optionally, the catalyst is a single-component platinum catalyst.
[0018] Optionally, the catalyst is used in an amount of 2000 to 6000 ppm based on the mass of the vinyl fluorosilicone oil.
[0019] On the other hand, the present invention also provides a method for preparing a one-component adhesive fluorosilicone gel, comprising:
[0020] The following components in parts by mass are mixed and degassed to obtain a single-component adhesive fluorosilicone gel:
[0021]
[0022] Optionally, the materials to be mixed and degassed also include 1 to 2 parts of a co-solvent;
[0023] The structural formula of the cosolvent is shown below:
[0024]
[0025] Among them, n is 2 to 6.
[0026] Beneficial effects:
[0027] (1) The one-component adhesive fluorosilicone gel of the present invention can be completely cured within half an hour at 150°C or above, is easy to use, and has very good high temperature resistance;
[0028] (2) The one-component adhesive fluorosilicone gel of the present invention has excellent oil resistance (solvent resistance) and good adhesion to PCB substrates, etc.;
[0029] (3) The present invention effectively improves the compatibility between substances in the system by adding a co-solvent of a specific structure to the single-component adhesive fluorosilicone gel, thereby significantly improving the transparency of the fluorosilicone gel after curing;
[0030] (4) The preparation method of the present invention is simple, and the single-component adhesive fluorosilicone gel has good acid and alkali resistance, a long low-temperature storage period and other advantages, and has excellent comprehensive performance. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below through examples. Through these examples, the features and advantages of the present invention will become clearer and more specific.
[0032] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.
[0033] In the present invention, the term "HMTETA" means 1,1,4,7,10,10-hexamethyltriethylenetetramine;
[0034] In the present invention, the term "THF" means tetrahydrofuran.
[0035] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0036] On the one hand, the present invention provides a one-component adhesive fluorosilicone gel, comprising the following components in parts by mass:
[0037]
[0038] It should be noted that silicone oil usually refers to linear polysiloxane products that remain in liquid state at room temperature, which are generally divided into two categories: methyl silicone oil and modified silicone oil. The most commonly used silicone oil is methyl silicone oil, also known as ordinary silicone oil, whose organic groups are all methyl, and its structure can be shown as follows: Methyl silicone oil has good chemical stability, insulation, and good hydrophobicity. Fluorosilicone oil is made by introducing F atoms into ordinary silicone oil. Fluorosilicone oil can be divided into methyl fluorosilicone oil, vinyl fluorosilicone oil, hydrogen-containing fluorosilicone oil and other types. Vinyl fluorosilicone oil means that the end and / or side of silicone oil (methyl silicone oil) contains vinyl and fluorine-containing groups. The fluorine-containing groups include but are not limited to fluorine-containing alkyl groups, including but not limited to -CF 3 、-CH 2 CH 2 CF 3 The terminal and side hydrogen-containing fluorosilicone oil refers to fluorosilicone oil with Si-H on both the terminal and side.
[0039] In order to achieve good environmental adaptability of some precision components in the environment of strong acid, strong alkali, organic solvent, etc., it is necessary to encapsulate and protect sensitive electronic components. The fluorine group is introduced into the side chain of methylsilane, which can improve its solvent resistance and acid and alkali resistance while ensuring a certain transparency, and ensure that the electronic components in this environment are not disturbed by the environment. The end-side hydrogen-containing fluorosilicone oil in the single-component adhesive fluorosilicone gel of the present invention is compounded with vinyl fluorosilicone oil, coupling agent, and catalyst, and each component is compounded in the above-mentioned mass parts, and the components are synergistically enhanced to obtain a single-component adhesive fluorosilicone gel with excellent comprehensive performance. The single-component adhesive fluorosilicone gel can be completely cured within half an hour at 150°C or above, has excellent high temperature resistance, oil resistance (solvent resistance), and has excellent bonding performance to PCB substrates.
[0040] As a preferred embodiment of the one-component adhesive fluorosilicone gel of the present invention, the one-component adhesive fluorosilicone gel further comprises 1 to 2 parts of a co-solvent;
[0041] The structural formula of the cosolvent is shown below:
[0042]
[0043] Among them, n is 2 to 6.
[0044] It should be noted that the inventors of the present application unexpectedly discovered through long-term research and development experiments that compounding the co-solvent of the above-mentioned structure with the aforementioned vinyl fluorosilicone oil, end-side hydrogen-containing fluorosilicone oil and other components can effectively improve the compatibility between substances in the system, thereby significantly improving the transparency of the fluorosilicone gel after curing. At the same time, the single-component adhesive fluorosilicone gel can maintain very good curing performance, high temperature resistance, solvent resistance (oil resistance), and has excellent bonding performance to PCB substrates.
[0045] In one embodiment of the aforementioned one-component adhesive fluorosilicone gel of the present invention, the molar content of vinyl in the vinyl fluorosilicone oil is 0.1-1%; the molar content of fluorine is 5-20%, preferably 10-20%, and more preferably 16-20%.
[0046] It should be noted that in the one-component adhesive fluorosilicone gel of the present invention, controlling the molar content of vinyl and fluorine in the vinyl fluorosilicone oil as above can further improve the performance of the one-component adhesive fluorosilicone gel, especially when the molar content of fluorine is preferably controlled to be 16-20%, the solvent (oil) resistance of the one-component adhesive fluorosilicone gel can be further significantly improved.
[0047] In another embodiment of the aforementioned one-component adhesive fluorosilicone gel of the present invention, the mass fraction of active hydrogen in the end-side hydrogen-containing fluorosilicone oil is 1-10%; the molar content of fluorine is 5-20%, preferably 16-20%.
[0048] It should be noted that in the one-component adhesive fluorosilicone gel of the present invention, controlling the mass fraction of active hydrogen and the molar content of fluorine in the end-side hydrogen-containing fluorosilicone oil as above can further improve the performance of the one-component adhesive fluorosilicone gel, especially when the molar content of fluorine in the end-side hydrogen-containing fluorosilicone oil is preferably controlled to be 16 to 20%, the solvent (oil) resistance of the one-component adhesive fluorosilicone gel can be further significantly improved.
[0049] In one embodiment of the aforementioned one-component adhesive fluorosilicone gel of the present invention, the coupling agent is one or more selected from fluorine-containing silane coupling agents.
[0050] It should be noted that when a fluorinated silane coupling agent is used as a coupling agent, the coupling agent and the vinyl fluorosilicone oil and the end-side hydrogen-containing fluorosilicone oil have better synergistic effects, and the single-component adhesive fluorosilicone gel obtains better performance.
[0051] In a preferred embodiment of the aforementioned one-component adhesive fluorosilicone gel of the present invention, the structural formula of the coupling agent is as follows:
[0052]
[0053] Among them, R 1 , R 2 is methyl and / or ethyl, and n is 2-6.
[0054] It should be noted that in the one-component adhesive fluorosilicone gel of the present invention, the coupling agent of the above structural formula is compounded with the aforementioned vinyl fluorosilicone oil and end-side hydrogen-containing fluorosilicone oil, and the comprehensive performance of the obtained one-component adhesive fluorosilicone gel is further improved.
[0055] In one embodiment of the aforementioned one-component adhesive fluorosilicone gel of the present invention, the catalyst is a one-component platinum catalyst.
[0056] In one embodiment of the aforementioned one-component adhesive fluorosilicone gel of the present invention, the amount of the catalyst used is 2000 to 6000 ppm based on the mass of the vinyl fluorosilicone oil.
[0057] It should be noted that in the one-component adhesive fluorosilicone gel of the present invention, a one-component platinum catalyst is used as a catalyst, and the amount of the catalyst is controlled as above, so that the one-component adhesive fluorosilicone gel can have excellent comprehensive performance. Specifically, the one-component platinum catalyst can be chloroplatinic acid or the like.
[0058] On the other hand, the present invention also provides a method for preparing a one-component adhesive fluorosilicone gel, comprising:
[0059] The following components in parts by mass are mixed and degassed to obtain a single-component adhesive fluorosilicone gel:
[0060]
[0061] It should be noted that the components such as vinyl fluorosilicone oil and end-side hydrogen-containing fluorosilicone oil are compounded according to the above-mentioned mass fractions, and a single-component adhesive fluorosilicone gel with excellent comprehensive performance can be prepared by mixing and degassing.
[0062] In one embodiment of the aforementioned preparation method of the present invention, the materials to be mixed and degassed further include 1 to 2 parts of a co-solvent;
[0063] The structural formula of the cosolvent is shown below:
[0064]
[0065] Among them, n is 2 to 6.
[0066] It should be noted that in the preparation method of the present invention, the co-solvent with the above-mentioned structure is mixed with the aforementioned vinyl fluorosilicone oil, end-side hydrogen-containing fluorosilicone oil and other components for degassing. The prepared single-component adhesive fluorosilicone gel can not only be completely cured within half an hour at 150°C or above, but also has excellent high temperature resistance and oil resistance (solvent resistance), and has excellent bonding properties to PCB substrates. In addition, the substances in the system are better compatible with each other, and the transparency of the fluorosilicone gel is greatly improved.
[0067] The present invention is further described in detail by way of examples below, but the present invention is not limited thereto. In the following examples, unless otherwise specified, the experimental instruments and raw materials involved are all commercially available products.
[0068] The sources of the reagents used in the following examples or comparative examples are described as follows:
[0069] Vinyl fluorosilicone oil, purchased from Xinyuan Chemical (Shandong) Co., Ltd., brand NFS7300, specific models are distinguished by the molar content of vinyl and fluorine;
[0070] The end-side hydrofluoric silicone oil was purchased from Xinyuan Chemical (Shandong) Co., Ltd. with the brand name NFS7400. The specific models are distinguished by the mass fraction of active hydrogen and the molar content of fluorine;
[0071] The end-containing hydrofluoric silicone oil was purchased from Xinyuan Chemical (Shandong) Co., Ltd., with the brand name NFS7401. The specific models are distinguished by the mass fraction of active hydrogen and the molar content of fluorine;
[0072] The side-containing hydrogen fluoride silicone oil was purchased from Shenzhen Guanheng New Material Technology Co., Ltd. with the brand name AFS-H-M1200. The specific models are distinguished by the mass fraction of active hydrogen and the molar content of fluorine.
[0073] Example 1
[0074]
[0075] In this embodiment:
[0076] The molar content of vinyl in the vinyl fluorosilicone oil used is 1%, and the molar content of fluorine is 15%;
[0077] The active hydrogen mass fraction of the end-side hydrogen-containing fluorosilicone oil used is 1%, and the molar content of fluorine is 15%;
[0078] The molecular structure of the coupling agent is shown below:
[0079]
[0080] Among them, R 1 and R 2 All are methyl, n is 3 to 6, and the synthesis method is as follows:
[0081] Add 48g of 3-glycidyloxypropyltrimethoxysilane to a 100ml three-necked flask, heat to 60°C, add 0.05g of tetrabutylammonium bromide, and drop 24g of hexanediol. Add the mixture over 40 minutes and react for 5 hours. Heat to 90°C, add 0.05g of tetrabutylammonium bromide, and drop 29g of fluorinated compound CF. 3 , add it in 30 minutes, react for 4 hours, then heat to 110℃ and degas for 1 hour, and control the vacuum degree at -0.04MPa to obtain the target coupling agent. The structural formula of the synthesized product is the above structural formula through nuclear magnetic hydrogen spectrum and other tests.
[0082] The catalyst is chloroplatinic acid.
[0083] The preparation method of this one-component adhesive fluorosilicone gel is as follows:
[0084] The above materials were weighed by mass and placed in a vacuum rotary degassing machine at a speed of 2000 r / min and a vacuum degree of -900 mbar for 1 minute to obtain the fluorosilicone gel.
[0085] Example 2
[0086]
[0087] In this embodiment:
[0088] The molar content of vinyl in the vinyl fluorosilicone oil used is 0.5%, and the molar content of fluorine is 20%;
[0089] The active hydrogen mass fraction of the end-side hydrogen-containing fluorosilicone oil used is 5%, and the molar content of fluorine is 20%;
[0090] The coupling agent is the same as in Example 1;
[0091] The catalyst is chloroplatinic acid.
[0092] The preparation method of the single-component adhesive fluorosilicone gel is the same as that of Example 1.
[0093] Example 3
[0094] A single-component adhesive fluorosilicone gel was prepared according to the component formula and method of Example 1, except that:
[0095] Also includes 1 part of co-solvent;
[0096] The structural formula of the cosolvent is shown below:
[0097] Where n is 2, the synthesis process of the cosolvent is as follows:
[0098] PDMS 65 -Br (20.0mg, 4.16μmol), monomer A (75mg, 0.208mmol), HMTETA (4.00mg, 4.00μL) and 500μL anisole were added to the polymerization tube in sequence, and the polymerization tube was placed in liquid nitrogen for freezing under nitrogen filling state, vacuumed after the sample was completely frozen, and then placed in warm water for stirring and thawing the sample under nitrogen filling state, and then the above operation was repeated three times, and then 4.12mg CuBr was added under liquid nitrogen freezing state, and then freezing-vacuuming-nitrogen filling was repeated, and the above operation was repeated three times, and the tube was sealed with an alcohol burner under the state of sample freezing and vacuuming. After the reaction system was melted at room temperature, it was placed in an 80℃ oil bath for polymerization. In the experiment, the polymerization degree was controlled by adjusting the feeding ratio of monomer and macromolecular initiator. After the reaction was completed, the reaction was quenched with liquid nitrogen. The obtained polymerization system was diluted with 10mL THF, and then the copper salt therein was removed with a neutral alumina column, and then precipitated with a large amount of methanol three times, and filtered to obtain an orange-yellow powder product. Through nuclear magnetic hydrogen spectrum and other tests, it was found that the structural formula of the synthesized product was the above structural formula.
[0099] Among them, PDMS 65 The structural formula of -Br is The synthesis process is as follows:
[0100] In a 250 mL round-bottom flask, add monohydroxy-terminated PDMS 65-OH (10.0g, 2.14mmol), triethylamine (0.428g, 4.28mmol) and 100mL of anhydrous THF were stirred and dissolved, and then placed in an ice-water bath for cooling. A mixture of bromoisobutyryl bromide (0.984g, 4.28mmol) and 20mL of anhydrous THF was slowly dripped into the above round-bottom flask. After the addition was completed, the reaction was continued in an ice-water bath for 1h, and then the ice-water bath was removed and the reaction was continued at room temperature for 48h. After the reaction was completed, the triethylamine salt was filtered to obtain a clear solution, and the colorless turbid liquid obtained was dissolved in 150mL of dichloromethane after THF was removed, and then washed 3 times with a saturated sodium bicarbonate solution, and the obtained organic phase was dried over anhydrous sodium sulfate. The dried organic phase was rotated to remove dichloromethane. Dissolve the product in 10 mL of THF and slowly drip it into 150 mL of methanol (it is best to place the methanol in a slender container, such as a chromatography column, so that the crude product can fully contact with the methanol and remove impurities therein). The product will separate from the methanol solution and stay in the lower layer. Repeat the above operation 5 times to obtain a colorless and transparent liquid, which is dried in vacuo at 60°C overnight.
[0101] PDMS 65 -OH was purchased from J&K Technology Co., Ltd.
[0102] Among them, the structural formula of monomer A is The synthesis method is as follows:
[0103] Add 422g D into a four-necked flask equipped with a thermometer and a stirrer. 3 F,121g Me 2 Vi SiCl and 12g hexamethylphosphoric triamine, heated to 50℃ for dehydration for 24h, then reacted at 120℃ for 2h, filtered the generated ammonium salt to obtain product 1, then added 100g trimethylsilyl chloride, 20g catalyst concentrated sulfuric acid at 50℃ for reaction for 24h, added 1g sodium carbonate for neutralization for 3-4h, after complete neutralization, heated to 180℃ for vacuum dehydration for 2h, filtered to obtain monomer A.
[0104] Example 4
[0105] A one-component adhesive fluorosilicone gel was prepared according to the components and method of Example 2, except that:
[0106] It also includes 1 part of a co-solvent, which is the same as the co-solvent in Example 3.
[0107] Comparative Example 1
[0108]
[0109] The vinyl fluorosilicone oil used has a vinyl content of 0.1% by mole and a fluorine content of 5% by mole;
[0110] The active hydrogen mass fraction of the end-side hydrogen-containing fluorosilicone oil used is 10%, and the molar content of fluorine is 5%;
[0111] The coupling agent is the same as in Example 1.
[0112] The catalyst is chloroplatinic acid.
[0113] The preparation method of the single-component adhesive fluorosilicone gel is the same as that of Example 1.
[0114] Comparative Example 2
[0115]
[0116] The molar content of vinyl in the vinyl fluorosilicone oil used is 0.5%, and the molar content of fluorine is 15%;
[0117] The active hydrogen mass fraction of the end-side hydrogen-containing fluorosilicone oil used is 7%, and the molar content of fluorine is 15%;
[0118] The coupling agent is the same as in Example 1;
[0119] The catalyst is chloroplatinic acid.
[0120] The preparation method of the single-component adhesive fluorosilicone gel is the same as that of Example 1.
[0121] Comparative Example 3
[0122]
[0123] The molar content of vinyl in vinyl fluorosilicone oil is 0.5%, and the molar content of fluorine is 15%;
[0124] The active hydrogen mass fraction of the end-side hydrogen-containing fluorosilicone oil used is 3%, and the molar content of fluorine is 15%;
[0125] The coupling agent is the same as in Example 1;
[0126] The catalyst is chloroplatinic acid.
[0127] The preparation method of the single-component adhesive fluorosilicone gel is the same as that of Example 1.
[0128] Comparative Example 4
[0129] The one-component adhesive fluorosilicone gel was prepared using the components and method of Example 1, except that:
[0130] The end-side hydrogen-containing fluorosilicone oil is changed into end-containing hydrogen-containing fluorosilicone oil and side hydrogen-containing silicone oil.
[0131]
[0132] In this comparative example:
[0133] The molar content of vinyl in the vinyl fluorosilicone oil used is 1%, and the molar content of fluorine is 15%;
[0134] The active hydrogen mass fraction of the end-containing hydrogen fluorosilicone oil used is 1%, and the molar content of fluorine is 15%; the active hydrogen mass fraction of the side-containing hydrogen fluorosilicone oil used is 1%, and the molar content of fluorine is 15%;
[0135] The coupling agent is the same as in Example 1;
[0136] The catalyst is chloroplatinic acid.
[0137] Comparative Example 5
[0138] The single-component adhesive fluorosilicone gel was prepared using the components and method of Example 2, except that:
[0139] The end-side hydrogen-containing fluorosilicone oil is changed into the end-side hydrogen-containing fluorosilicone oil and the end-containing hydrogen silicone oil.
[0140]
[0141] In this comparative example:
[0142] The molar content of vinyl in the vinyl fluorosilicone oil used is 0.5%, and the molar content of fluorine is 20%;
[0143] The active hydrogen mass fraction of the end-containing hydrogen fluorosilicone oil used is 5%, and the molar content of fluorine is 20%; the active hydrogen mass fraction of the end-side containing hydrogen fluorosilicone oil used is 5%, and the molar content of fluorine is 20%;
[0144] The coupling agent is the same as in Example 2;
[0145] The catalyst is chloroplatinic acid.
[0146] Comparative Example 6
[0147] The one-component adhesive fluorosilicone gel was prepared using the components and method of Example 1, except that:
[0148] The end-side hydrogen-containing fluorosilicone oil is the same as the end-side hydrogen-containing fluorosilicone oil, the mass fraction of active hydrogen in the end-side hydrogen-containing fluorosilicone oil is 1%, and the molar content of fluorine is 15%.
[0149] Comparative Example 7
[0150] The single-component adhesive fluorosilicone gel was prepared using the components and method of Example 2, except that:
[0151] The hydrogen-containing fluorosilicone oil on the change end side is the same as the hydrogen-containing fluorosilicone oil on the side side, the mass fraction of active hydrogen in the hydrogen-containing fluorosilicone oil on the side side is 5%, and the molar content of fluorine is 20%.
[0152] Test Example 1
[0153] In order to examine the high temperature resistance of the one-component adhesive fluorosilicone gel prepared in the above examples and comparative examples, the one-component adhesive fluorosilicone gel prepared in the above examples and comparative examples was poured into a circular mold with a diameter of 3 mm, cured in an oven at 150°C for 1 hour, and then placed in an oven at 250°C for 5 minutes for high temperature aging test. The results were observed with a magnifying glass, and the relevant test results are shown in Table 1.
[0154] Table 1 High temperature resistance test results
[0155]
[0156]
[0157] From the results in Table 1, it can be seen that the colloid cracking of Comparative Examples 1 and 2 is mainly due to the excessive ratio of Si-H / Si-Vi (end-side hydrogen fluorosilicone oil / vinyl fluorosilicone oil) in the system, that is, the cross-linking agent (end-side hydrogen fluorosilicone oil) accounts for too much, resulting in the colloid being too hard after curing and easy to crack after high-temperature aging. In Comparative Examples 4 and 5, the side-containing hydrogen fluorosilicone oil or the end-side hydrogen fluorosilicone oil accounts for too little, and it cannot be cured normally at 150°C for 1h. Although it can be cured after 250°C for 5min, the overall strength is low, so bubbles are generated. In Comparative Example 6, there is only end-containing hydrogen fluorosilicone oil, which only plays a role in increasing the growth of the molecular chain, and cannot play a role in cross-linking between molecular chains, so it cannot be cured normally even after high-temperature aging; in Comparative Example 7, there is only side-containing hydrogen fluorosilicone oil, which plays a role in cross-linking between molecular chains, but there is no end-containing hydrogen fluorosilicone oil, and there are too many cross-linking points, resulting in the gel being too hard and having no toughness. Although it can be cured normally, the entire colloid state is a tofu dregs state after aging, and it is completely cracked. The single-component adhesive fluorosilicone gel of the present invention can be completely cured within half an hour at 150° C. or above, is easy to use, and has very good high temperature resistance.
[0158] Test Example 2
[0159] In order to investigate the oil resistance of the one-component adhesive fluorosilicone gel prepared in the aforementioned embodiments and comparative examples, the one-component adhesive fluorosilicone gel in the aforementioned embodiments and comparative examples was poured into a 2cm×2cm×2cm mold, cured in an oven at 150°C for 1h, and then completely immersed in n-pentane solvent. The test was carried out under a test environment of 23°C and 50% air humidity. The relevant test results are shown in Table 2 below.
[0160] Table 2, n-pentane immersion test results:
[0161]
[0162] From the results in Table 2, it can be seen that the greater the fluorine content, the lower the mass change rate after 8 days of immersion, indicating that the solvent resistance is more excellent. The gels that cannot be cured under the conditions of 150°C and 1 hour (Comparative Examples 4, 5 and 6) cannot be used for this immersion test.
[0163] Test Example 3
[0164] In order to examine the bonding performance of the one-component adhesive fluorosilicone gel in the aforementioned embodiments and comparative examples, the one-component adhesive fluorosilicone gel was bonded to PCB, a common substrate for electronic adhesives. The relevant test results are shown in Table 3.
[0165] Adhesive performance test method: directly apply the glue to the PCB board, cure it at 150℃ for 1h, then take the PCB board out of the oven, cool it to room temperature, and use a knife to scrape the contact surface between the glue and the PCB board to observe whether it is bonded.
[0166] Table 3, PCB board bonding
[0167]
[0168]
[0169] From the results in Table 3, it can be seen that when the coupling dosage is 1.5 or 2 parts, the adhesion to the substrate PCB is good, and when the coupling dosage is 1 part, there is a situation of non-adhesion or unstable adhesion. The gel that cannot be cured under the conditions of 150°C and 1h (Comparative Examples 4, 5 and 6) cannot be used for the adhesion performance test.
[0170] Test Example 4
[0171] In order to investigate the effect of the co-solvent on the transparency of the one-component adhesive fluorosilicone gel, the transmittance of the one-component adhesive fluorosilicone gel in the above Examples 1 to 4 was tested. The fluorosilicone gel was cured into a 2 cm × 2 cm × 2 mm sheet in a mold, and the transmittance was tested according to the method for using a UV-visible spectrophotometer. The relevant test results are shown in Table 4.
[0172] Table 4. Transmittance test results
[0173] Example Example 1 Example 2 Example 3 Example 4 Curing conditions 150℃×1h 150℃×1h 150℃×1h 150℃×1h Transmittance(%) 87 86 98 98
[0174] The results in Table 4 show that the addition of co-solvent can effectively improve the compatibility of substances in the system, thereby significantly improving the transparency of the cured fluorosilicone gel.
[0175] In the description of the present application, it should be noted that the terms "upper", "lower", "inside", "outside", "front", "back", "left", "right", etc. indicate directions or positional relationships based on the directions or positional relationships in the working state of the present application. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limitations on the present application.
[0176] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "install", "connect" and "connect" should be understood in a broad sense. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0177] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. A one-component adhesive fluorosilicone gel, characterized in that: Contains the following components by mass:
2. The one-component adhesive fluorosilicone gel according to claim 1, characterized in that: The one-component adhesive fluorosilicone gel also includes 1 to 2 parts of a solvent; The structural formula of the cosolvent is shown below: Among them, n is 2 to 6.
3. The one-component adhesive fluorosilicone gel according to claim 1, characterized in that: The molar content of vinyl in the vinyl fluorosilicone oil is 0.1-1%; the molar content of fluorine is 5-20%, preferably 10-20%, and more preferably 16-20%.
4. The one-component adhesive fluorosilicone gel according to claim 1, characterized in that: The mass fraction of active hydrogen in the end-side hydrogen-containing fluorosilicone oil is 1-10%; the molar content of fluorine is 5-20%, preferably 16-20%.
5. The one-component adhesive fluorosilicone gel according to claim 1, characterized in that: The coupling agent is one or more selected from fluorine-containing silane coupling agents.
6. The one-component adhesive fluorosilicone gel according to claim 5, characterized in that: The structural formula of the coupling agent is shown below: Wherein, R1 and R2 are methyl and / or ethyl, and n is 2-6.
7. The one-component adhesive fluorosilicone gel according to claim 1, characterized in that: The catalyst is a single-component platinum catalyst.
8. The one-component adhesive fluorosilicone gel according to claim 7, characterized in that: The dosage of the catalyst is 2000-6000ppm based on the mass of the vinyl fluorosilicone oil.
9. A method for preparing a one-component adhesive fluorosilicone gel, characterized in that: include: The following components in parts by mass are mixed and degassed to obtain a single-component adhesive fluorosilicone gel:
10. The preparation method according to claim 9, characterized in that: The materials for mixed degassing also include 1 to 2 parts of co-solvent; The structural formula of the cosolvent is shown below: Among them, n is 2 to 6.